2019
DOI: 10.1021/acs.biomac.9b01331
|View full text |Cite|
|
Sign up to set email alerts
|

Marcromolecular Architecture and Encapsulation of the Anticancer Drug Everolimus Control the Self-Assembly of Amphiphilic Polypeptide-Containing Hybrids

Abstract: Macromolecular architecture plays an important role in the self-assembly process of block copolymer amphiphiles. Herein, two series of stimuli-responsive amphiphilic 3-miktoarm star hybrid terpolypeptides and their corresponding linear analogues were synthesized exhibiting the same overall composition and molecular weight but different macromolecular architecture. The macromolecular architecture was found to be a key parameter in defining the morphology of the nanostructures formed in aqueous solutions as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 85 publications
1
4
0
Order By: Relevance
“…Interestingly, hybrids based on the linear PEG showed almost no partially cleaved intermediates, indicating that the rate limiting step of its degradation and disassembly is the escape from the micelles and once encountered outside of the micelles by the enzyme, it can get fully cleaved. Higher stability of the V-shaped architecture toward complete enzymatic degradation was also reported recently by Iatrou and co-workers, which reported triblocks containing linear or V-shaped poly­(ethylene oxide) (PEO) as the terminal block, poly­( l -histidine- co -γ-benzyl- l -glutamate) as the hydrophobic block, and poly­( l -lysine hydrochloride) as the second terminal hydrophilic block. The reported V-shape containing PEG triblocks self-assembled into vesicles and micelles that showed higher stability toward enzymatic degradation in comparison with the linear PEG containing analogues.…”
Section: Resultssupporting
confidence: 78%
“…Interestingly, hybrids based on the linear PEG showed almost no partially cleaved intermediates, indicating that the rate limiting step of its degradation and disassembly is the escape from the micelles and once encountered outside of the micelles by the enzyme, it can get fully cleaved. Higher stability of the V-shaped architecture toward complete enzymatic degradation was also reported recently by Iatrou and co-workers, which reported triblocks containing linear or V-shaped poly­(ethylene oxide) (PEO) as the terminal block, poly­( l -histidine- co -γ-benzyl- l -glutamate) as the hydrophobic block, and poly­( l -lysine hydrochloride) as the second terminal hydrophilic block. The reported V-shape containing PEG triblocks self-assembled into vesicles and micelles that showed higher stability toward enzymatic degradation in comparison with the linear PEG containing analogues.…”
Section: Resultssupporting
confidence: 78%
“…To determine the molar mass ( M n and M w ) and the dispersity index ( Đ , or else PDI), measurements by SEC were performed utilizing Chloroform at 25 °C at a flow rate of 1 mL/min. The SEC system was composed of a Waters 600 high-performance liquid chromatographic pump, Waters Ultrastyragel columns HR-1, HR-2, HR-4E, HR-4, and HR-5, and a Shimadzu RID-10A refractive index detector.…”
Section: Methodsmentioning
confidence: 99%
“…The transformation of the secondary structure of the block-graft copolypeptide is due to PHIS, which has pKa = 6.5. In a previous work, we have found that PHIS adopts a β-turn conformation at pH higher than 7.4, while it transforms to random coil by lowering the pH and becoming protonated [26][27][28][29][30]. Figure 15 provides the Circular Dichroism data for the PLL 78 -b-(PLL 10 -g-PHIS 15 ) at pH values 5.0, 6.5, and 7.4.…”
Section: Study Of the Secondary Structure Of Pll 78 -B-(pll 10 -G-phimentioning
confidence: 95%